Inafectación del impuesto a la renta de las actividades de comercialización de las fuerzas armadas y el cumplimiento de sus metas y objetivos período 2001-2010 - Zapata Periche, Simón (2013)
The present basic research, seeks to determine whether the free of Income Tax of the marketing activities of goods and services that they perform the entities of the Armed Forces, which do not constitute the state's business; determines the compliance of their institutional goals and objectives. We worked with a descriptive of the type design quantitative, non-experimental, longitudinal retrospective, addressing each of the factors mentioned above, the budget was analyzed by sources of funding allocated by the Ministry of Economy and Finance to the entities of the Armed Forces during the period 2001 to 2010, synthesizing these allocations; as well as the variables that influence the compliance with the institutional goals and objectives. As a result, the need has been identified to improve the diagnosis of training needs in order to achieve the design of a strategy of customized training to run the resources allocated by the Ministry of Economy and Finance, as well as the recruitment and employment of the additional revenue (resources directly collected), with greater efficiency, effectiveness and transparency; as well as the negative influence in the media (equipment) that provides the entity to the administrative staff to develop their administrative work, the same that is directly related to the results and/or achievement of organizational goals and objectives.